Measurement of the strontium triplet Rydberg series by depletion spectroscopy of ultracold atoms - Couturier, Luc; Weidemüller, Matthias (Physical review, 2019)
We report on the atom loss spectroscopy of strontium Rydberg atoms in a magnetooptical trap, using a two-photon excitation scheme through the intermediate state 5s5p3P1. Energies of the 5sns3S1 and 5snd3D1,2 Rydberg series of 88Sr in the range 13≤n≤50 are determined with an absolute accuracy of 10 MHz, including the perturbed region where the 5snd3D2 series couples to the 5snd1D2 series. This represents an improvement by more than two orders of magnitude compared to previously published data. The quantum defects for each series are determined using the extended Rydberg-Ritz formula in the range where there is no strong perturbation. A value of 1377012721(10)MHz for the first ionization limit of 88Sr is extracted.